2003
DOI: 10.2169/internalmedicine.42.7
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress and Diabetes Mellitus.

Abstract: Pancreatic p-cells are strongly engaged in protein secretion and have highly developed endoplasmic reticulum (ER). Proper folding of polypeptide into a threedimensional structure is essential for cellular function and protein malfolding can threaten cell survival.Various conditions can perturb the protein folding in the ER, which is collectively called ER stress. In order to adapt ERstress conditions, the cells respond in three distinct ways such as transcriptional induction of ER chaperones, translational att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 51 publications
2
103
0
2
Order By: Relevance
“…[2][3][4][5] Recent studies show that hepatic ER stress is observed in metabolic diseases such as obesity and diabetes.…”
Section: Abstract Gomisin N; Endoplasmic Reticulum (Er) Stress; Hepamentioning
confidence: 99%
“…[2][3][4][5] Recent studies show that hepatic ER stress is observed in metabolic diseases such as obesity and diabetes.…”
Section: Abstract Gomisin N; Endoplasmic Reticulum (Er) Stress; Hepamentioning
confidence: 99%
“…Because of its function as a secretory cell, the beta cell is characterised by a highly developed ER and high levels of ER stress transducer proteins, including inositol requirement 1 (IRE1), RNAdependent protein kinase-like ER kinase (PERK) and immunoglobulin heavy chain binding protein (BiP). Studies have shown that the beta cell is one of the most susceptible cells to ER stress, and furthermore, ER stress-mediated apoptosis in the beta cell has been suggested as having an important role in the development of type 2 diabetes [28,29]. In fact, diabetes has been labelled by some as a protein misfolding disease [30], indicating the substantial responsibility the ER has in the correct functioning of the beta cell.…”
Section: Possible Mechanisms That Could Explain Hypersecretion-inducementioning
confidence: 99%
“…High levels of glucose also induce expression of CHOP (C/EBP Homologous protein), which causes a decrease in intracellular pH linked to increased activity of pro-apoptotic protein BAX. 5,6 Increased expression of BAX subsequently aids release of cytochrome c from mitochondria. Prolonged activation of ER stress response activates ER stress induced apoptosis pathway.…”
Section: Introductionmentioning
confidence: 99%